Evaluating the sensitivity and specificity of the UK and Dutch growth referral criteria in predicting the diagnosis of pathological short stature - MARTIN O SAVAGE; Lee Martin; Gemma White; Helen L Storr; Shakira Cosier; Afiya Andrews; Ruben Willemsen (BMJ Publishing Group, 2022)
Objective The aim of this observational study was to evaluate the UK and Dutch referral criteria for short stature to determine their sensitivity and specificity in predicting pathological short stature. Adherence to the recommended panel of investigations was also assessed.Study design Retrospective review of medical records to examine the auxological parameters, investigations and diagnosis of subjects referred to two paediatric endocrine clinics at the Royal London Children's Hospital between 2016 and 2021. We analysed: height SD score (HtSDS), height SDS minus target height SDS (Ht-THSDS) and height deflection SDS (HtDefSDS). The UK referral criteria were HtSDS <−2.7, Ht-THSDS >2.0 and HtDefSDS >1.3. The Dutch referral criteria were HtSDS <−2.0, Ht-THSDS >1.6 and HtDefSDS >1.0.Results Data were available for 143 subjects (72% males) with mean (range) age 8.7 years (0.5-19.9). HtSDS and Ht-THSDS were significantly lower in the pathological stature (n=66) versus the non-pathological stature (n=77) subjects (−2.67±0.82 vs −1.97±0.70; p<0.001 and −2.07±1.02 vs −1.06±0.99; p<0.001, respectively). The sensitivity and specificity to detect pathology was 41% and 83% for the UK criteria (HtSDS <−2.7) compared with 59% and 79% for the Dutch criteria (HtSDS <−2.0), 48% and 83% for UK criteria (Ht-THSDS <−2.0) compared with 74% and 72% for Dutch criteria (Ht-THSDS <−1.6) and 33% and 68% for UK criteria (HtDefSDS >1.3) compared with 44% and 63% for the Dutch criteria (HtDefSDS >1.0). On average, each patient had 88% of the recommended investigations, and 53% had all the recommended testing. New pathology was identified in 36% of subjects.Conclusions In isolation, the UK auxological referral thresholds have limited sensitivity and specificity for pathological short stature. The combination of HtSDS and Ht-THSDS improved the sensitivity of UK criteria to detect pathology from 41% to 68%. Attention to the child's genetic height potential prior to referral can prevent unnecessary assessments.